Nursing technologies for patient safety in intensive care: a systematic review (Research, Society and Development, 2022)
This article aims to demonstrate the evidence that nursing care technologies ensure the safety of patients admitted to Intensive Care Units. Systematic review with search in six databases. Two researchers selected the texts independently in the first stage; and, in the second stage, in a conciliation meeting, the conflicts were analyzed by a third researcher. In order to evaluate the level of agreement, the Kappa coefficient was applied; in order to evaluate the risk of bias and classify the levels of evidence, the Grading of Recommendations, Assessment, Development and Evaluation was adopted. Observational studies were also evaluated with the risk of bias in non-randomized studies of interventions. The 23 included studies were evaluated regarding their quality of evidence, with very low evidence ranking determined for most studies (16/69.6%), moderate evidence for five studies (21.7%), one study with low evidence (4.3%) and one study as high evidence (4.3%). Patient safety is essential, but, despite this commitment, only one study (4.3%), about thermometry assessment, showed high level of evidence that nursing care technologies ensure patient safety in the Intensive Care Unit setting.